Impact of Nurse Peer Review on a Culture of Safety. Issue 2 (April 2019) - Herrington, Cynthia R.; Hand, Mikel W.
Abstract : Background: Nursing peer review (NPR) is essential in evaluating nursing practice. A common theme throughout the literature is that NPR holds nurses accountable for their practice. Problem: The nursing profession has struggled to conduct peer review consistently due to lack of a standardized framework. Approach: A NPR program was developed, implemented, and evaluated in a 355-bed acute care hospital in the Midwestern United States. Outcomes: A pre- and postdesign using the Agency for Healthcare Research and Quality Hospital Survey on Patient Safety Culture was used for evaluation. Paired t test results revealed statistically significant differences in group means for 2 questions: mistakes have led to positive changes here ( P < .001, d = 1.31), and staff will freely speak up ( P = .002, d = 0.67). Clinically significant differences in group means were noted for the remaining survey items. Conclusions: Implementation of an NPR program is a promising means to improve the culture of safety in health care institutions. Abstract : Supplemental Digital Content is Available in the Text.